2017
DOI: 10.1080/13696998.2017.1405817
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the medical revenue of comprehensive pricing reform in Chinese urban public hospitals after removing drug markups: case of Nanjing

Abstract: Nanjing's reform represents successful pricing and compensation reform in Chinese urban public hospitals. It is recommended that a differentiated and dynamic compensation plan should be established in accordance with the revenue structure of different hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…We excluded 25 records that did not meet our inclusion criteria. Nine studies (included time series study, retrospective cohort study, and quasi-experimental study) were included in this systematic review [1][2][3][4][6][7][8][9][10]. The characteristics of the included studies are summarized in Table 3.…”
Section: Characteristics Of the Included Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…We excluded 25 records that did not meet our inclusion criteria. Nine studies (included time series study, retrospective cohort study, and quasi-experimental study) were included in this systematic review [1][2][3][4][6][7][8][9][10]. The characteristics of the included studies are summarized in Table 3.…”
Section: Characteristics Of the Included Trialsmentioning
confidence: 99%
“…In addition, He et al (2018) showed the results that pharmaceutical reform could not reduce total health expenditure in long term [3]. There was a statistical significantly positive correlation between the rate of services compensation and the proportion of medical service revenue [1]. However, Mao et al (2019) concluded that no significant change of the average medical expenditure per prescription was observed [10].…”
Section: Total Expensesmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] A few existing studies have been conducted to evaluate the impacts of PRDMS-C, after it took effect in different areas in China, such as Sanming [34], Zhejiang [35], Hubei [36,26], Guangxi [37], etc. Most of the studies showed that the reform reduced drug cost whereas its effectiveness in containing medical expenditures was questionable with some unintended consequences [38][39][40][41][42][43]. For example, through the DID approach, Fu et al [34] analyzed the public hospital reform in Sanming and showed that the Sanming model was able to reduce drug cost and total medical expenditures without measurably sacrificing the quality or the efficiency of health service provision.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some previous studies on the effects of PRDMS-C, the fundamental differences between county-level and urban hospitals limited the generalizability of conclusions of those previous studies on county-level hospitals to urban ones. Although several literatures presented preliminary evaluations in urban cities like Nanjing [42], Beijing [43], etc., the conclusions from these studies can hardly reflect countrylevel effects of the reform in general as the evidence from the selected locations can hardly be generalized to other areas with different economic and health development background.…”
Section: Introductionmentioning
confidence: 99%